ANDROID-BASED SMART SYSTEM FOR FRUIT SELECTION TO PREVENT TODDLER STUNTING - Riansah, Wahyu; Lumban Gaol, Nur Yanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Preventing stunting in toddlers is crucial for improving children's health and growth. Stunting occurs due to chronic nutritional deficiencies during the first 1,000 days of a child's life, affecting their height, cognitive development, and immune system, which can reduce their future potential. Fruits play an important role in a toddler's diet because they are rich in vitamins, minerals, fiber, antioxidants, and other bioactive compounds that support physical growth and brain development. However, selecting the right fruits is vital because some fruits can cause digestive issues or allergies in toddlers. To assist parents in choosing the right fruits, a mobile-based expert system using the Certainty Factor method has been developed. This system provides recommendations based on the toddler's health condition and evaluates the nutritional content of fruits. With this system, parents can ensure that their toddlers receive optimal nutrition, contributing to stunting prevention and ensuring that the toddlers grow up healthy, intelligent, and with full potential in the future Choosing the right fruits and maintaining a balanced nutrition are crucial parts of supporting the sustainability of stunting prevention efforts. Keywords: certainty factor method; expert system; fruit selection; stunting prevention; toddler nutrition Abstrak: Pencegahan stunting pada batita sangat penting untuk meningkatkan kualitas kesehatan dan pertumbuhan anak. Stunting terjadi akibat kekurangan gizi kronis pada 1.000 hari pertama kehidupan batita, memengaruhi tinggi badan, perkembangan kognitif, dan sistem imun anak, yang berisiko mengurangi potensi masa depan mereka. Buah-buahan memiliki peran penting dalam pola makan batita, karena kaya akan vitamin, mineral, serat, antioksidan, dan senyawa bioaktif yang mendukung pertumbuhan fisik dan perkembangan otak. Namun, pemilihan buah yang tepat sangat penting karena beberapa buah dapat menyebabkan masalah pencernaan atau alergi pada batita. Untuk membantu orang tua dalam memilih buah yang sesuai, dikembangkan sistem pakar berbasis mobile dengan metode Certainty Factor. Sistem ini memberikan rekomendasi berdasarkan kondisi kesehatan batita, serta mengevaluasi kandungan nutrisinya. Dengan sistem ini, orang tua dapat memastikan bahwa batita mendapatkan nutrisi yang optimal dengan berkontribusi dalam pencegahan stunting dengan memastikan batita tumbuh sehat, cerdas, dan memiliki potensi penuh di masa depan. Pemilihan buah yang tepat dan nutrisi yang seimbang menjadi bagian penting dalam mendukung upaya keberlanjutan pencegahan stunting. Kata kunci: batita; metode certainty factor; pemilihan buah; pencegahan stunting; sistem cerdas